A survey of parabens in commercial pharmaceuticals from China and its implications for human exposure. (October 2016) - Ma, Wan-Li; Zhao, Xue; Lin, Zhong-Yang; Mohammed, Mohammed O.A.; Zhang, Zi-Feng; Liu, Li-Yan; Song, Wei-Wei; Li, Yi-Fan
Abstract: Parabens are widely used as antimicrobial preservatives during pharmaceutical production. However, little information is available regarding the occurrence of parabens in commercial pharmaceuticals and their implications for human exposure. In this study, six commonly used parabens were analyzed by ultra-performance liquid chromatography-tandem mass spectrometry with 100 commercial pharmaceuticals collected from China. Almost all of the pharmaceutical samples contained at least one kind of parabens with the detection frequency of 97%. The concentrations of Σ6 parabens (sum of the six parabens) ranged from below MDL to 1256 ng/g, with mean and median values of 94.8 and 119 ng/g, respectively. Methyl paraben (MeP), ethyl paraben (EtP) and propyl paraben (PrP) were the predominant compounds. Significant positive correlation was observed between concentrations of MeP and PrP, indicating their co-applications in pharmaceuticals. Levels of Σ6 parabens varied in different categories of pharmaceuticals and increased with their shelf lives. Based on the measured concentrations and daily ingestion rates of pharmaceuticals, the estimated daily intake ( EDI ) of parabens was calculated. The median values of EDI pharmaceutical for male adults, female adults and children were 4.05, 4.75 and 9.73 ng/kg-bw/day, respectively, which were three orders of magnitude lower than those from foodstuffs and personal care products (PCPs). It was firstly reported that the total exposure dose was 0.326 mg/kg-bw/day via foodstuffs, PCPs, and pharmaceuticals for Chinese female adults. Graphical abstract: Highlights: Parabens were frequently detected in commercial pharmaceuticals in China. MeP, EtP and PrP were the predominant parabens. Parabens levels varied with different categories of pharmaceuticals. Exposure to parabens via pharmaceuticals was much lower than foodstuffs and PCPs. Future work is needed to estimate exposure to parabens with comprehensive sources.